Imam Ali in German Orientalism - Niemah Sahi Hasan ALmawswii ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2020)
Imam Ali (pbuh) was one of the few who penetrated the thought of the laws of time and place and the geography of belonging, it is in its human dimensions a source of wisdom, justice and rhetoric and the conscience of a giant Sami and a revolution of freedom, and therefore his character is the focus of the eyes of philosophers, writers, poets and thinkers in the world and the source of love and inspiration and appreciation and respect of Before anyone knew something about his biography and his heroism and creative thinking along the path of the human fair and different intellectual and belief. Therefore, the study seeks to monitor the reflection of the image and personality of Imam Ali (pbuh) in the writings of German orientalists, after the German Orientalist school of the leading schools in contrast to this concept, unlike other European Orientalist schools, both in its old and classic Oriental productions or in its modern and contemporary productions, Through two main axes The first is concerned with discovering the nature of the Islamic narrative heritage and thus the quality of the culture reflected and the extent of its influence on the subject of the research, and the second is interested in monitoring some Orientalist models and the speech on the personality of Imam(pbuh)